(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The study of socio-political views of al-Farabi acquires a greater relevance in contemporary context of increasing democratic reforms, creation of a legal and secular state, approval of harmony in society. At this point, the study of al Farabi’s political philosophy, especially his teachings on politics, freedom, happiness, the necessity of mutual aid among people, his appeal to science, intellectual and moral perfection of human and society, are being overly actualized. Particularly, the concept of political leadership of the thinker, his ideas about the virtuous society, justice, equality, keeping peace, preventing war, condemnation of unjust wars, are relevant today. In this regard, political philosophy and ideas of the thinker can be a valuable source for the political education of the younger generation. Key words: Socio-political philosophy of Farabi, ethics, tracts, state, philosophy, motive, wisdom, humanity, saturated society, «virtuous» and «ignorant» city, etc.